2021
DOI: 10.1097/ju.0000000000001766
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Biopsy of the Prostate can Be Omitted in Men with PI-RADS™ 5 and Prostate Specific Antigen Density Greater than 15%

Abstract: Purpose: We evaluated the prostate cancer and clinically significant prostate cancer detection on systematic biopsy (SB), target biopsy (TB) alone and combined SB and TB in men with Prostate Imaging Reporting and Data SystemÔ (PI-RADSÔ) 5 lesion. Materials and Methods: From a prospectively maintained prostate biopsy database, we identified consecutive patients with PI-RADS 5 lesion on multiparametric magnetic resonance imaging. The patients underwent multiparametric magnetic resonance imaging followed by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 28 publications
3
32
1
Order By: Relevance
“…Lahoud et al [9] found that perilesional biopsies yielded csPCa even when the target was negative. Finally, Tafuri et al [20] found that for PI-RADS 5 lesions with a PSA density of >0.15, systematic samples did not provide additional diagnostic yield. A compilation of evidence led the PI-RADS Committee to recommend targeted biopsy of the ROI and a 5-mm penumbra for PI-RADS 4 and 5 lesions [11].…”
Section: Discussionmentioning
confidence: 99%
“…Lahoud et al [9] found that perilesional biopsies yielded csPCa even when the target was negative. Finally, Tafuri et al [20] found that for PI-RADS 5 lesions with a PSA density of >0.15, systematic samples did not provide additional diagnostic yield. A compilation of evidence led the PI-RADS Committee to recommend targeted biopsy of the ROI and a 5-mm penumbra for PI-RADS 4 and 5 lesions [11].…”
Section: Discussionmentioning
confidence: 99%
“…We selected different thresholds of mPSAD to obtain similar performance in our series of PI-RADS 3 than that of Görtz et al [22,81]. The use of appropriate thresholds in different populations has been previously described for mPSAD [19][20][21][82][83][84][85][86][87][88][89][90][91][92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the combination of MRI lesions and serum markers in PCa diagnosis, a recent report showed a detection rate in CS PCa detection for TB of 81% in PIRADS 5 patients. When the authors focused on PSA density > 0.15ng/mL 2 sub-population, TB had a detection rate of 91%, and only three CS PCa patients were missed if SB was omitted [ 32 ]. Similarly, Lee et al found in the same patients’ category that only 4 (5%) patients with any cancer and 6 (8%) patients with CS PCa would be missed if SB was omitted [ 33 ].…”
Section: Discussionmentioning
confidence: 99%